2019
DOI: 10.1186/s12884-019-2312-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of bacterial vaginosis and associated risk factors in pregnant women receiving antenatal care at the Kumba Health District (KHD), Cameroon

Abstract: Background Bacterial vaginosis (BV) is a common reproductive tract disorder in women of child bearing age, accounting for one third of vaginal infections. It is characterized by an increase in vaginal pH, decreased Lactobacilli, and overgrowth of facultative and anaerobic bacteria. Studies have consistently shown BV to be a risk factor for adverse obstetric and gynecological outcomes. BV is believed to play a critical role in the transmission of sexually transmitted infections. Its aetiology and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
13
3
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 36 publications
(49 reference statements)
9
13
3
7
Order By: Relevance
“…Higher prevalence of vaginal infection in all the age groups could be due to the fact that women are more sexually active and some of them have many sexual partners, whether they are married or not, in addition to the poor hygiene conditions. ese results are in accordance with those of Kamga et al [7] and Achondou et al [8] in Cameroon. e high prevalence of these infections could be due to the anatomy of the female vaginal organ which favours penetration and the installation of the infection and poor personal hygiene.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Higher prevalence of vaginal infection in all the age groups could be due to the fact that women are more sexually active and some of them have many sexual partners, whether they are married or not, in addition to the poor hygiene conditions. ese results are in accordance with those of Kamga et al [7] and Achondou et al [8] in Cameroon. e high prevalence of these infections could be due to the anatomy of the female vaginal organ which favours penetration and the installation of the infection and poor personal hygiene.…”
Section: Discussionsupporting
confidence: 93%
“…12.02% of the symptomatic patients presented recurrent symptoms of nonspecific vaginitis. e prevalence of multiple infections was lower in this study than that reported by others [7,8]. However, G. vaginalis was frequently associated with C. albicans (9.49%).…”
Section: Discussioncontrasting
confidence: 68%
“…Concomitant infection between TV and G. vaginalis and TV and C. albicans were found in 3 women, respectively. The concomitant infection is commonly found in cases where TV makes the vaginal environment susceptible to infection by C. albicans, and other microorganisms, such as G. vaginalis joins leading to the development of bacterial vaginosis (BV) [24][25][26][27][28][29][30]. The presence of atypical squamous cells of unknown significance was observed in 10 of the sample population, and HPV characteristic lesions were observed in 14 women, and among them, 5/24 of women who show lesion on the pap smear, were infected concomitantly with TV.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Alcendor (12) investigated health disparities in BV and its implications for HIV-1 acquisition in African-American women and reported prevalence rates of 52% and 32% among Black and Mexican American women respectively. Kamga et al (13) reported a prevalence rate of 26% among pregnant women in Cameroon. In comparison, Nduati et al (14) reported a prevalence rate of 47% in a cohort of HIV-positive pregnant women receiving care in Kenya.…”
Section: Introductionmentioning
confidence: 99%
“…However, the actual mechanisms underlying BV and the associated risk factors are still poorly understood (16). It is crucial to note that BV could a ict non-pregnant and pregnant women (13,16) and can also occur in both sexually-active and -inactive young women (17), and in young and older women. Still, it is more pronounced among younger women (18).…”
Section: Introductionmentioning
confidence: 99%